Mediterranean diet and cognitive function in older age: results from the Women’s Health Study - Samieri, Cécilia (2013)
BACKGROUND: Adherence to a Mediterranean diet may help prevent cognitive decline in older age, but studies are limited. We examined the association of adherence to the Mediterranean diet with cognitive function and decline. METHODS: We included 6,174 participants, aged 65+ years, from the cognitive sub-study of the Women’s Health Study. Women provided dietary information in 1998 and completed a cognitive battery 5 years later, followed by two assessments at 2-year intervals. The primary outcomes were composite scores of global cognition and verbal memory. The alternate Mediterranean diet adherence 9-point-score was constructed based on intakes of: vegetables, fruits, legumes, whole grains, nuts, fish, red and processed meats, moderate alcohol, and the ratio of monounsaturated-to-saturated fats. RESULTS: After multivariable adjustment, the alternate Mediterranean diet score was not associated with trajectories of repeated cognitive scores (P-trend across quintiles=0.26 and 0.40 for global cognition and verbal memory, respectively), nor with overall global cognition and verbal memory at older ages, assessed by averaging the three cognitive measures (P-trend=0.63 and 0.44, respectively). Among alternate Mediterranean diet components, higher monounsaturated-to-saturated fats ratio was associated with more favorable cognitive trajectories (P-trend=0.03 and 0.05 for global cognition and verbal memory, respectively). Greater whole grain intake was not associated with cognitive trajectories, but was related to better average global cognition (P-trend=0.02). CONCLUSIONS: In this large study of older women, we observed no association of the Mediterranean diet with cognitive decline. Relations between individual Mediterranean diet components, particularly whole grains, and cognitive function merit further study.